The codebreaker's secret - Ackerman, Sara (Mira, 2022)
A brilliant female codebreaker. An "unbreakable" Japanese naval code. A pilot on a top-secret mission that could change the course of WWII. The Codebreaker's Secret is a dazzling story of love and intrigue set during America's darkest hour.